The Hsp90 Inhibitor 17-DMAG Attenuates Hyperglycemia-Enhanced Hemorrhagic Transformation in Experimental Stroke - Zhang, Jiaming (Biomed Res Int, 2021)
INTRODUCTION: Hemorrhagic transformation (HT) is one of the most common complications of ischemic stroke which is exacerbated by hyperglycemia. Oxidative stress, inflammatory response, and matrix metalloproteinases (MMPs) have been evidenced to play a vital role in the pathophysiology of HT. Our previous study has reported that 17-DMAG, an Hsp90 inhibitor, protects the brain against ischemic injury via inhibiting inflammation and reducing MMP-9 after ischemia. However, whether 17-DMAG would attenuate HT in hyperglycemic middle cerebral artery occlusion (MCAO) rats is still unknown. METHODS: Acute hyperglycemia was induced by an injection of 50% dextrose. Rats were pretreated with 17-DMAG before MCAO. Infarction volume, hemorrhagic volume neurological scores, expressions of inflammatory molecules and tight junction proteins, and activity of MMP-2 and MMP-9 were assessed 24 h after MCAO. RESULTS: 17-DMAG was found to reduce HT, improve neurological function, and inhibit expressions of inflammatory molecules and the activation of MMPs at 24 h after MCAO. CONCLUSION: These results implicated that Hsp90 could be a novel therapeutic target in HT following ischemic stroke.